under root 1 + tan squared theta into under root 1 + cot square theta into under root 1 - cos square theta into under root 1 minus sin square theta
Answers
Answered by
10
please send image of your question.........
Answered by
5
under root 1+tan ^2 theta =under root sec ^2 theta = sec theta
by this process under root 1 + cot^2 = cosec theta
root under 1 - cos ^2 theta = sin theta
root under 1-sin^2 theta= cos theta
then according to question
under root 1 + tan squared theta into under root 1 + cot square theta into under root 1 - cos square theta into under root 1 minus sin square theta=
cosec theta × sec theta × sin theta × cos theta
= 1 answe
by this process under root 1 + cot^2 = cosec theta
root under 1 - cos ^2 theta = sin theta
root under 1-sin^2 theta= cos theta
then according to question
under root 1 + tan squared theta into under root 1 + cot square theta into under root 1 - cos square theta into under root 1 minus sin square theta=
cosec theta × sec theta × sin theta × cos theta
= 1 answe
Similar questions
Science,
7 months ago
Social Sciences,
7 months ago
Geography,
7 months ago
India Languages,
1 year ago
Hindi,
1 year ago
Economy,
1 year ago